The Influence of Organization Citizen Behavior and Employee Compensation on The Performance of Employee Contract Regional Revenue Agency Pekanbaru - Haji Mustaqim; M. Toni; Abdul Syukur Rahman (LAFADZ JAYA Publisher, 2022)
This study aims to determine how much Organization Citizen Behavior and employee compensation have on the performance of contract employees in enforcing and confiscating local taxes at the Pekanbaru City Regional Revenue Agency, either partially or simultaneously. This writing contains the results of a study entitled The Influence of Organization Citizen Behavior and Employee Compensation on the Performance of Contract Employees in the Collection and Confiscation of Local Taxes which I did at the Regional Revenue Agency of Pekanbaru City. This type of research uses a descriptive method with a quantitative approach. The data used in this research is primary data. The population in this study were 40 employees and the sampling technique used was saturated sample, the respondents in this study were 40 contract employees, the data collection technique used a questionnaire, the data processing technique used the SPSS version 21 program. The analytical method used was the classical assumption test (Test Normality, Multicollinearity Test, Heteroscedasticity Test), multiple linear regression analysis, hypothesis testing (t test and F test) and the coefficient of determination. The results of research with multiple linear regression analysis. Organizational citizen behavior and compensation simultaneously influence employee performance with a significance level of 0.305. Organizational behavior has a partial effect on employee performance with a significance level of 0.000 <0.05, which means the hypothesis is accepted, compensation has a partial effect on employee performance with a significance level of 0.000 <0.05, which means the hypothesis is accepted.